Creating cohesive communities: using Conditional–Collective–Community-Based Incentives to change social norms on polio immunization in Pakistan - Tabassum, Farhana; Delawalla, Zayaan; Mirani, Mushtaq; Khan, Zahid Ali; Muhammad, Aadarsh Fateh; Asim, Muhammad; Das, Jai K. (Frontiers in Public Health, 2025)
Immunization remains a critical public health strategy, particularly in countries like Pakistan where vaccine-preventable diseases are prevalent despite global efforts to eradicate poliomyelitis. This study investigates the role of community engagement (CE) and conditional incentives in increasing polio vaccine uptake in High-Risk Union Councils (HRUCs) of Pakistan. Utilizing an exploratory qualitative research design, the study was conducted to assess the impact of an intervention which involved participatory CE, including the formation of Community Health Committees (CHCs) that conducted community sessions, made home visits, and implemented the Conditional–Collective–Community-Based Incentives (C3Is) in HRUCs in Bannu and Karachi, Pakistan to reduce the rate of refusals for the oral polio vaccine (OPV). These conditional incentives were based on the reduction of polio vaccine refusals by 30 and 50% in specific clusters during the first and second phase of the trial. The findings indicate that leveraging community influencers to change the social norms of the community through CE and C3Is lead to collective behavioral changes. CE served as an effective tool for dispelling myths while also providing a springboard to build community connections and cohesion. Furthermore, this change was accelerated by the provision of conditional communal non-cash incentives, leading to a significant improvement in polio immunization coverage and a reduction in the rate of vaccine refusals. The study underscores the importance of integrating context specific innovative community-specific strategies to overcome vaccine hesitancy and achieve immunization goals in challenging environments and when the target of polio eradication cannot be realized with business as usual.